Motivational Interdependence in Couple Relationships - Pusch, Sebastian; Schönbrodt, Felix D.; Zygar-Hoffmann, Caroline; Hagemeyer, Birk (Frontiers in Psychology, 2022)
This article presents an integrative conceptual model of motivational interdependence in couples, the MIC model. Based on theoretical tenets in motivation psychology, personality psychology, and research on interpersonal perception, the MIC model postulates that two partners’ motive dispositions fundamentally interact in shaping their individual motivation and behavior. On a functional level, a partner’s motivated behavior is conceptualized as an environmental cue that can contribute to an actor’s motive expression and realization. However, the partner’s motivated behavior is considered to gain this motivational relevance only via the actor’s subjective perception. Multilevel analyses of an extensive experience sampling study on partner-related communal motivation (N = up to 60,803 surveys from 508 individuals nested in 258 couples) supported the MIC model. Participants, particularly those with strong communal motive dispositions, behaved more communally at moments when they perceived their partners to behave more communally. In addition, participants experienced momentary boosts in satisfaction when they behaved more communally and, at the same time, perceived their partners’ behavior as similarly communal. Broader implications of the MIC model for research on romantic relationships are discussed.